Nursing Students’ Perceptions of Barriers, Facilitators and Solutions in Their Role as Health Promoters: Findings from a Qualitative Study - Gloria Modena; Beatrice Mazzoleni; Anna Sponton; Orejeta Diamanti; Giovanna Artioli; Gaia Monti; Valentina Negri; Federica Dellafiore (Nursing Reports, 2025)
Background: Nurses play a crucial role in health promotion (HP) policy and in encouraging healthy behaviors. However, challenges persist in effectively integrating HP as a core component of healthcare systems and nursing practice. Therefore, it is essential to develop specialized and advanced competencies in nursing students, incorporate HP into nursing academic curricula, and better understand the factors influencing nursing students’ development of these competencies—an area that remains underexplored. Accordingly, this study explores and describes the factors nursing students perceive as essential in developing competencies in HP and in fulfilling their role as health promoters. Methods: A qualitative study was conducted using Reflexive Thematic Analysis. Data were collected through semi-structured interviews with 19 nursing students. Results: Five main themes emerged: (1) Training Needs of Future Health Promoters, (2) Navigating Time Constraints in Health Promotion, (3) Nurses’ Awareness of Their Role in HP, (4) Perceived Need to Adopt Healthier Lifestyles, and (5) Challenges of Lifestyle Management. Key facilitators included strong mentorship and well-structured educational programs; barriers included insufficient clinical exposure and time constraints. Additionally, students emphasized the need for HP to be a core aspect of nursing curricula. While acknowledging existing obstacles, participants also identified practical solutions that could be integrated into training and practice to enhance the impact of HP in nursing care. Conclusions: The study highlights significant gaps in HP education for nursing students and the need for curriculum reforms to better prepare them as health promoters. Future research should consider the perspectives of clinical mentors and evaluate the effectiveness of innovative teaching methods—such as simulation-based training—in strengthening students’ HP competencies.